2022
DOI: 10.3390/ijms23158671
|View full text |Cite
|
Sign up to set email alerts
|

Tyro3 Targeting as a Radiosensitizing Strategy in Bladder Cancer through Cell Cycle Dysregulation

Abstract: Bladder cancer is a common cancer; it is the tenth most common cancer in the world. Around one fourth of all diagnosed patients have muscle-invasive bladder cancer (MIBC), characterized by advanced tumors and which remains a lethal disease. The standard treatment for MIBC is the bladder removal by surgery. However, bladder-preserving alternatives are emerging by combining chemotherapy, radiotherapy and minimal surgery, aiming to increase the patient’s quality of life. The aim of the study was to improve these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several studies depicted that the aberrant TYRO3 expression in tumor cells effectively enhances the proliferation and migration of tumor cells [ 22 , 23 ]. Therefore, the expression of TYRO3 would be aberrantly activated with tumorigenesis and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies depicted that the aberrant TYRO3 expression in tumor cells effectively enhances the proliferation and migration of tumor cells [ 22 , 23 ]. Therefore, the expression of TYRO3 would be aberrantly activated with tumorigenesis and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…TYRO3 has been considered carcinogenic and a potential therapeutic target for GC, 13,14 whereas studies have indicated the role of TYRO3 in other solid tumors. 15,16 Regarding the combined regulatory role of the TAM family in tumorigenesis and tumor development, targeting aberrant TYRO3 expression in GC may be a new cancer treatment strategy. A study reported that TYRO3 regulated colorectal cancer cell proliferation, migration, and invasion through the AKT-mTOR pathway.…”
mentioning
confidence: 99%